Regeneration of a Multipurpose Woody Legume - Acacia auriculiformis through Mature Tree Nodal Explants (Plant Tissue Culture and Biotechnology, 2024)
Multiple shoots have been induced in nodal explants of 30-year-old Acacia auriculiformis trees on Nitsch's medium (N medium) supplemented with 1.0 mg/l N6-benzyladenine. Addition of 0.1 mg/l adenine sulfate to N medium containing BA, enhanced the caulogenic response whereby the number of shoots developing on each node increased from three to fifteen. Plantlets were obtained by rooting axenically raised shoots on N medium (half strength) with 1.0 mg/l naphthalene acetic acid. Use of activated charcoal (0.01%) in the medium completely suppressed callus formation at the root-shoot junction.Plant Tissue Cult. & Biotech. 34(1): 1-10, 2024 (June)